A Narrative of the Adventures and Escape of Moses Roper, from American Slavery. - Roper, Moses (Distributed for the University of North Carolina at Chapel Hill Library., 2011)
The Narrative of the Adventures and Escape of Moses Roper can be read as an extended autobiographical meditation on the meaning of race in antebellum America. First published in England, the text documents the life of Moses Roper, beginning with his b.